A case report: primary CNS angiitis - Holay, Madhuri P.; Game, Prasad D.; Kharkar, Sandip; Chudalwar, Piyush (International Journal of Research in Medical Sciences, 2017)
The primary angiitis of the central nervous system (PACNS) is an entity with a very low incidence and prevalence. It affects small and medium sized arteries of the brain parenchyma, spinal cord and leptomeniges resulting in CNS dysfunction. It is defined by inflammation of the cerebral vasculature without angiitis of other organ. Its clinical manifestations are very heterogeneous and make clinical diagnosis difficult. In most cases, a brain biopsy is required. Only the clinical suspicion and the ability to recognize the possible clinical and imagenological patterns of presentation make an accurate diagnosis possible. We hereby report a case of Primary angiitis of CNS in 35 year old right handed male who presented with ischemic stroke with Left Hemiplegia. The diagnosis of PACNS was made after ruling out most of the causes of secondary CNS angiitis.